Propulsive Integration on a Search and Rescue Drone Aircraft - Alrifai, Yasser; Avetian, Hayk-David; Ingemarsson, Carl; Kadi, Oliver; Mathiesen, Victor; Vassilev, Maria (My University, 2022)
The propulsive system is an integral part of any aerial vehicle because it is responsible for producing thrust, which in turn is what allows the vehicle to move through the air. This project investigates and implements a propulsive system to a search and rescue drone aircraft by developing a selection and combination of propellers and motors that will best serve for a given mission. The process for selecting motors and propellers is done by comparing existing products on the market with each other and examining their torque- and efficiency matching. Only a few of the top candidates are selected for further investigation with a testing rig in a wind tunnel, which in turn results in a few suitable combinations of motors and propellers for the dedicated mission and aerodynamic loads. From these results suggestions are made for how the propellers can be modified for a better fit for this specific application. Interesting follow-up projects could include further research by developing new propellers specifically for the application. Additionally, interesting follow-up projects could include further investigation of what kind of motor is optimal, and what batteries can be used and implemented into the drone aircraft.
Keywords: UAV; Propeller; Motor; Thrust; Torque; Efficiency; Propeller-Motor matching; Energy consumption